Outcomes of high BMI colorectal cancer patients with natural orifice specimen extraction surgery: a propensity-score matching study - Zhang, Chenkai; Zhang, Hao; Li, Wenyang; Yu, Songtao; Qi, Haonan; Wang, Chunlin; Artur, Ibatullin; Wang, Guiyu (Frontiers in Surgery, 2025)
BackgroundNatural orifice specimen extraction surgery (NOSES) is widely used for colorectal cancer. However, there is limited study regarding the outcomes of patients with high BMI who undergo NOSES surgery for colorectal cancer.MethodsThis retrospective study included 251 patients (including 205 Non-High BMI and 46 High BMI patients) who underwent NOSES for colorectal cancer between January 2013 and December 2018. Outcomes related to surgery, anal function and long-term survisval were compared between the Non-High BMI and High BMI patients with the propensity-score matching (PSM) method. Age, gender, tumor location (sigmoid/rectum), preoperative CEA, CA199, T stage and N stage were considered as covariates for PSM.ResultsAfter matching, 44 patients in the Non-High BMI group and 44 patients in the High BMI group were eligible for analysis. No significant differences were observed between the groups in terms of operative time, blood loss, time to first flatus, time to first diet, postoperative hospital stays, positive margin, postoperative complication, conversion to open surgery and pathological outcomes (all P-value > 0.05). Besides, there was no significant difference for anal function 6 months after surgery between the two groups (P = 0.723). The overall survival (OS) and disease-free survival (DFS) for the Non-high BMI group were comparable to those for the High BMI group (P = 0.156 for OS, P = 0.266 for DFS).ConclusionWith careful preoperative evaluation, High-BMI patients can successfully undergo NOSES surgery and achieve favorable outcomes.